2011
DOI: 10.1227/neu.0b013e3181fdf912
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique and Outcomes in the Treatment of Spinal Cord Ependymomas: Part II: Myxopapillary Ependymoma

Abstract: The goal of surgical treatment of myxopapillary ependymomas is resection to the greatest extent possible with preservation of function. In cases of subtotal resection, postoperative radiation therapy may improve outcome. If neurological function is maintained at treatment, these indolent lesions allow years of good function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 15 publications
2
36
0
6
Order By: Relevance
“…Males outnumbered females at a ratio of 1.5:1. The most common presenting symptom was back pain, 6,13,23,35 mostly of dull intensity and restricted to the lower back. Some patients reported a pseudoradicular component as well.…”
Section: Discussion Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Males outnumbered females at a ratio of 1.5:1. The most common presenting symptom was back pain, 6,13,23,35 mostly of dull intensity and restricted to the lower back. Some patients reported a pseudoradicular component as well.…”
Section: Discussion Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Akyurek and colleagues 2 found no difference in the overall survival rate or progression free-survival rate between patients treated by GTR and those treated by STR. Likewise, Kucia and colleagues 20 reported no difference in the outcomes of patients treated by GTR alone versus STR followed by radiotherapy. In contrast, Sonneland and colleagues 35 showed that GTR was associated with lower Tumor control after surgery for spinal myxopapillary ependymomas: distinct outcomes in adults versus children overall recurrence rates and improved overall survival than was STR alone.…”
Section: ©Aans 2013mentioning
confidence: 96%
“…1,6,16,23,[27][28][29]32 In total, 28 articles with 475 patients were included in this integrative analysis. [2][3][4][5][7][8][9][10][11][12][13][14][15][17][18][19][20][21][23][24][25][26]30,31,[34][35][36][37] …”
Section: Article Selectionmentioning
confidence: 99%
See 2 more Smart Citations